Efficacy of Antibiotic‐Loaded Hydroxyapatite/Collagen Composites Is Dependent on Adsorbability for Treating Staphylococcus aureus Osteomyelitis in Rats. Issue 4 (17th November 2019) - Egawa, Satoru; Hirai, Keigo; Matsumoto, Rempei; Yoshii, Toshitaka; Yuasa, Masato; Okawa, Atsushi; Sugo, Ken; Sotome, Shinichi
Abstract : This study aimed to investigate the feasibility of local antibiotic administration using hydroxyapatite collagen (HAp/Col) composite as a drug delivery system. Minomycin, teicoplanin, and vancomycin showed antibacterial effects up to 14 days after subcutaneous implantation in rats with HAp/Col owing to their adsorbability. The implantation of HAp/Col impregnated with vancomycin for an acute osteomyelitis model revealed a significant therapeutic effect because of longitudinal antibacterial activity. These results indicated that the adsorbability of antibiotics onto the carrier is important when locally administered. ABSTRACT: Osteomyelitis remains one of the most challenging disorders for orthopedic doctors despite the advancement of therapeutic techniques. The purpose of this study was to investigate the feasibility of local antibiotic administration using hydroxyapatite/collagen (HAp/Col) as a drug delivery system. We hypothesized that higher adsorbability of antibiotics onto HAp/Col will result in more efficacious activity and therefore, treatment of osteomyelitis. Eight antibiotics were examined in this study: amikacin, cefazolin, cefotiam, daptomycin, minocycline, piperacillin, teicoplanin, and vancomycin. Aligning with their adsorbability onto HAp/Col, minocycline, teicoplanin, and vancomycin showed antibacterial effects up to 14 days after subcutaneous implantation in Wistar rats; while antibiotics with reduced adsorbability (cefazolin, cefotiam, piperacillin) had diminished antibacterial effects. Furthermore, when implanted into a rat femur, vancomycin levels from the Hap/Col were detected in the medullary space above the minimum inhibitory concentration for Staphylococcus aureus for 7 days, while cefazolin levels were undetectable. Aligning with these results, implantation of Hap/Col impregnated with vancomycin to the femur in an acute osteomyelitis rat model had a greater therapeutic effect than cefazolin, as measured by the number of bacteria, the extent of bone destruction, and bone regeneration. These results indicated that the adsorbability of antibiotics onto their carrier is important when locally administered and that HAp/Col scaffolds might be a useful antibiotic delivery system for osteomyelitis. © 2019 The Authors. Journal of Orthopaedic Research® published by Wiley Periodicals, Inc. on behalf of Orthopaedic Research Society J Orthop Res 38:843‐851, 2020